Destination Branding of Ternate City in Communicating the Tourism Values - Anisa Kadriah Sabanur Liandri; Hifni Alifahmi (Jobmark: Journal of Branding and Marketing Communication, 2021)
Destination branding is a concept that aims to build or improve the quality of a tourist destination. Ternate is one of the destinations in eastern Indonesia with potential in the tourism sector and is currently actively developing strategies to increase tourist visits. This article investigates the efforts of the Ternate tourism board in building a destination branding strategy to promote Ternate's tourism potential. Data was collected using observation methods and in-depth interviews with tourism officials and local community members. The results of this study reveal that the Ternate City Tourism Office applies destination branding by building integrated tourist destinations to become national tourism objects.